c.2 - Higgins, Benjamin (ed.) (Boston, 1988)
(In this important book, leading international researchers in regional economic development have contributed an integrated set of chaptersreviewing the whole field. The book is in honour to Francois Perroux whose two important concepts in economics, time and space, have been pivotal. His essay on growth poles was seminal, giving rise to much research activity and to government programs for regional development..The book comprises five parts. Part 1 covers Perroux s work in general and growth poles in particular. Part 2 deals with the politics of space and population and regional economics. Part 3 deals with Canadian scene at national and regional levels. In Part 4 chapters on urban development; small and medium-size cities and capital grants in the experience of other countries. Part 5 concludes the book with chapters on growth poles; optimal size of cities, of regional disparities and government intervention.A major book making a substantial contribution to the literature of
Keywords: Regional economic